Maker culture and science teaching: An experience report with biology degree students - Lima, Luiz Paulo Fernandes; Lima, José Ricardo Barros de; Menezes, Daniel Brandão; Vasconcelos, Francisco Herbert Lima (Seven Editora, 2024)
Digital production offers scientific educators and their students a multitude of opportunities, ranging from computational modeling to the production of educational materials. Thus, this report outlines the experiences during a formative phase of maker culture and digital fabrication with students in the third semester of the biology course at the Federal University of Ceará - UFC. The training covered the introduction of maker culture, computational modeling processes and 2D and 3D digital manufacturing, culminating in the conceptualization of projects that could potentially be carried out in the future within a FabLab. Throughout the training, the participants' involvement was palpable, evident in the use of educational materials, responses to the questionnaire and suggestions for future projects. Consequently, we deduce that the results signify a positive reception and lucid understanding among participants about the potential of FabLab and digital fabrication in education. DOI:https://doi.org/10.56238/sevened2024.010-022